HUBUNGAN ANTARA PERSEPSI SISWA TERHADAP KOMPETENSI GURU DAN PENGGUNAAN ALAT PERAGA DENGAN KECAKAPAN PSIKOMOTORIK SISWA SEKOLAH MENENGAH KEJURUAN (SMK) - Najmulmunir, Nandang; Suharyat, Yayat; Haryono, Pauzan (Edukasi, 2009)
The purpose of the research is to analyze the relationship between student perception for teacher competence and using of learning medium with students psychomotor skill. The study was conducted at 70 samples selected randomly. The result of the research indicates that there are positive correlations between : (1) student perception for teacher competence and students psychomotor skill; (2) students perception for using of learning medium; moreover, there is positive correlation between students perception for teachers competence and using of learning medium with students psychomotor skill.